Ensino de Astronomia na educa??o profissional e superior por meio de kit did?tico baseado em seguidor solar - Ara?jo, Marcos Silva (2024)
The purpose of this work is to encourage the teaching of Astronomy at the Professional and Higher Education levels through the development of a Practical Activities Guide for the construction of an educational kit based on solar trackers. These solar trackers, used to optimize solar energy conversion by directing photovoltaic panels, parabolic collectors, and sensors such as pyrheliometers, monitor solar parameters along the Sun?s apparent path in the sky. Introducing these kits into the educational environment will allow students to acquire interdisciplinary knowledge in Astronomy, electronics, and programming. The adopted teaching methodology is Project-Based Learning (PBL), a pedagogical strategy that engages students in solving real-world problems, fostering creativity, collaboration, and critical thinking. The research aims to understand the impact of these educational kits on students? learning experiences, exploring their perceptions, motivations, and knowledge acquisition in the classroom. The study focuses on two target groups: students from the Computer Engineering course at Universidade Salvador (UNIFACS) and students from the Professional Education in Electromechanics and Electrotechnics at the Centro Estadual de Educa?c?ao Profissional Aureo de Oliveira Filho (CEEP), both located in Feira de Santana, ? BA.